Solvent‐Induced Control over Breathing Behavior in Flexible Metal–Organic Frameworks for Natural‐Gas Delivery - Kundu, Tanay; Wahiduzzaman, Mohammad; Shah, Bhuvan B.; Maurin, Guillaume; Zhao, Dan (Angewandte Chemie, 2019)
Finding appropriate stimuli for controlling the breathing behavior of flexible metal–organic frameworks (MOFs) is highly challenging. Herein, we report the solvent‐induced changes in the particle size and stability of different breathing phases of the MIL‐53 series, a group of flexible MOFs. A water/dimethylformamide (DMF) ratio is tuned to synthesize members of the MIL‐53 series which have different behaviors. The breathing is explored by high‐pressure methane sorption tests. Increasing DMF concentration decreases MOF particle size and increases the stability of the porous phases, boosting the 5.8–65 bar sorption difference of methane, which is required for natural‐gas delivery. Atmen lernen: Die Änderung des Wasser/DMF‐Verhältnisses bei der Synthese von Metall‐organischen Gerüsten (MOFs) der flexiblen MIL‐53‐Serie führte zu unterschiedlichen Atmungseigenschaften, die durch Hochdruck‐Methansorptionstests untersucht wurden. Bei Zunahme der DMF‐Konzentration verringert sich die Partikelgröße und erhöht sich die Stabilität der porösen Phasen, was mit einem Anstieg der Methanspeicherkapazität von 5.8 auf 65 bar einhergeht.